Evaluasi Program Pendidikan Karakter di Pendidikan Anak Usia Dini - Apriani, Reni; Anriani, Nurul (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2024)
Human being was created for the purpose of serving God with religion being the guide. Everyone must do self-introspection (muhasabah) to achieve these goals every year, month, day, or even every time. This study aims to evaluate the program of character education implemented in and achieved by PAUD Insan Karimah. This is qualitative research with the CIPP model (context, inputs, process, and product). The data were collected through in-depth interviews, document studies, and structured observations. The subjects in this study were the principal, class teacher, and art assistant teacher. The results showed that the program of character education at PAUD Insan Karimah was in the good category. This was shown by the completion of aspects of context, input, process, and product, as evidenced by the inclusion of character in the school's vision and mission, the existence of supporting facilities and infrastructure, the integration of programs through habituation activities, and the involvement of all parties in character education programs.